Comparative study of Satisfaction and Problems of Face to Face and Online Mode of Learners - Farkhanda Rasheed Chaudhary (International Islamic University Islamabad, 2019)
The technological advancements have great impact on teaching and learning. The modes of education have been modified in this era where course offerings, teaching and assessment are done through online resources such as Learning Management Systems (LMS). This paper is focused to explore and compare the satisfaction and problems of face to face and online mode of leaners regarding content, interaction with the instructor and other students, assessment and evaluation. Quantitative research design was used for this study, where survey method was used to collect data. A sample of 156 BS computer science students was selected through random sampling. The data was collected through questionnaire. Overall, majority of the students were satisfied with different features of online mode of learning like content, assessment and evaluation, modes of interaction and delivery but a lower percentage of student’s satisfaction was found regarding their interaction with the instructor. It is recommended that more research should be conducted in order to explore other parameters like student’s achievements and grades in online learning programs. Universities should offer more virtual and online programs for the enhancement of higher education.